2013
DOI: 10.5812/hepatmon.6215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge and Practice of Hairdressers in Women’s Beauty Salons in Isfahan About Hepatitis B, Hepatitis C, and AIDS in 2010 and 2011

Abstract: BackgroundBlood-borne viruses such as hepatitis B, hepatitis C, and human immunodeficiency virus (HIV) have some common epidemiological characteristics, and have infected millions of people throughout the world. Patients infected by acute hepatitis or HIV infections may not be aware of the disease, and thereby cause transmission to others. During haircut, shave, or pedicure, barbers may accidentally expose to their clients’ blood, transmit their own infection to them, or transmit the infection from one client … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 8 publications
3
24
1
2
Order By: Relevance
“…The present study showed that more than 80% of beauticians were well informed regarding viral hepatitis, which was higher than that reported by staff of women's beauty salons from Iran, manicurists from Sã o Paulo State (Brazil), and beauticians from Australia [Murtagh and Hepworth, 2004;Oliveira and Focaccia, 2010;Ataei et al, 2013]. It is most likely that the knowledge regarding viral hepatitis observed in the present study was due to the health campaigns carried out in previous years in our country.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The present study showed that more than 80% of beauticians were well informed regarding viral hepatitis, which was higher than that reported by staff of women's beauty salons from Iran, manicurists from Sã o Paulo State (Brazil), and beauticians from Australia [Murtagh and Hepworth, 2004;Oliveira and Focaccia, 2010;Ataei et al, 2013]. It is most likely that the knowledge regarding viral hepatitis observed in the present study was due to the health campaigns carried out in previous years in our country.…”
Section: Discussioncontrasting
confidence: 73%
“…Several studies have demonstrated that the knowledge of viral hepatitis varies among beauticians. Murtagh and Hepworth [] reported poor knowledge about hepatitis C transmission among beauticians from Australia, but Amodio et al [] and Ataei et al [] demonstrated a good level of knowledge about hepatitis B and C among hairdressers from Italy and Iran, respectively. Beauty salons are common in Brazil, and there is information exchange among professionals and their clients; therefore, a good level of knowledge among beauticians could contribute to improve knowledge among their clients.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended that future efforts should be directed at training and influencing the attitudes of hairdressing employers (25). A study by Ataei et al showed that, staffs of women's beauty salons in Isfahan had intermediate knowledge about blood borne pathogens and recommended more education for increasing knowledge of hairdressers (26). In this study we tried to clarify how interventional education impacts employee health risks and conditions and causes improvement in many aspects of hairdressing.…”
Section: Discussionmentioning
confidence: 99%
“…O desenvolvimento econômico do país e os meios de comunicação têm influenciado o aumento da renda e trazendo consigo padrões de imagem e beleza, atingindo todas as camadas sociais, faixas etárias e ambos os sexos. Tal condição tem inspirado os indivíduos a se preocuparem com a qualidade de vida, sobretudo, quanto aos cuidados com o corpo, sendo, necessário o crescimento quantitativo de profissionais que possam atender esta demanda, incluindo as manicures e pedicures 1 A ausência de uma padronização na realização do processo de esterilização prejudica e interfere na eficácia e no uso destes materiais. Para que o processo de esterilização seja totalmente efetivo, a temperatura e o tempo são imprescindíveis e devem ser rigorosamente respeitados, levando-se em consideração que o termo "esterilização" se refere ao processo que elimina todas as formas microbianas de vida 22 .…”
Section: Introductionunclassified